2021
DOI: 10.1109/access.2021.3121998
|View full text |Cite
|
Sign up to set email alerts
|

Network Anomaly Detection With Temporal Convolutional Network and U-Net Model

Abstract: Anomaly detection in network traffic is one of the key techniques to ensure security in future networks. Today, the importance of this topic is even higher, since the network traffic is growing and there is a need to have smart algorithms, which can automatically adapt to new network conditions, detect threats and recognize the type of the possible network attack. Nowadays, there are a lot of different approaches, some of them have reached relatively sufficient accuracy. However, the majority of works are bein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Although the accuracy of [ 12 ] is 99.7% better than our paper, the paper does not use all datasets for training and testing, so it cannot be compared with our paper. Compared with [ 5 , 6 , 9 , 10 , 17 ], the proposed model effectively improves the detection performance.…”
Section: Experimental Results and Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…Although the accuracy of [ 12 ] is 99.7% better than our paper, the paper does not use all datasets for training and testing, so it cannot be compared with our paper. Compared with [ 5 , 6 , 9 , 10 , 17 ], the proposed model effectively improves the detection performance.…”
Section: Experimental Results and Analysismentioning
confidence: 99%
“…For example, the authors of [ 26 ] randomly selected 40,000 benign data (the total number of benign traffic data was 13,484,708) and 20,000 attack data to conduct experiments. The authors of [ 6 ] used nine of the ten files for their experiments. In this study, we used all datasets for experimental evaluation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For anomaly detection, He et al suggested combining a Multimodal Deep Auto Encoder (MDAE) and an LSTM [34]. UNSW-NB15, NSL-KDD, and CICIDS2017 datasets are used to test this exclusive approach, and accuracy scores for multiclass classi cation were 98.60%, 86.20%, and 80.20% respectively.Mezina et al employed a U-Net and a temporal CNN trained onCICIDS2018 and KDD99 datasets to identify network threats [35]…”
Section: Related Workmentioning
confidence: 99%